The effect of olsalazine of chinese generic drugs on ulcerative colitis induced by dextran sulfate sodium salt in BALB/c mice - Zheng-Yong Yu; Yu-Sheng Xu; Miao Tang; Wen-Feng Xin (Acta Cirúrgica Brasileira, 2023)
ABSTRACT Purpose: To explore effect and mechanism of olsalazine of Chinese generic drugs on ulcerative colitis induced by dextran sulfate sodium salt (DSS) in BALB/c mice. Methods: The mouse model of ulcerative colitis was induced by free drinking of 3% (w/v) DSS aqueous solution for seven days. The mice were treated with olsalazine (0.6 g·kg-1) of Chinese generic drugs. The therapeutic effect of olsalazine on ulcerative colitis mice was evaluated by measuring disease activity index (DAI), colonic mucosal injury index (CMDI), histopathological score (HS), and detected the expression levels of interleukin (IL)-2, IL-10, tumor necrosis factor-α (TNF-α), interferon-γ (IFN-γ), IL-1β in serum and IL-7, IL-17, IL-22, epidermal growth factor (EGF), transforming growth factor β1 (TGF-β1) in colonic homogenate of mice. Results: Olsalazine significantly increased the contents of IL-2, IL-10, IL-22, TGF and EGF in ulcerative colitis rats, and significantly decreased the scores of DAI, CMDI, HS and the contents in IL-7, IL-17, TNF-α, IL-1β and IFN-γ when compared with the model group. It improved the degree of colonic lesion in ulcerative colitis mice. Conclusions: It was suggested that olsalazine has a therapeutic effect on ulcerative colitis induced by DSS in mice, and the mechanism may be related to the increase of IL-2, IL-10, IL-22, TGF, and EGF and the decrease of the expression of IL-7, IL-17, TNF-α, IL-1β, and IFN-γ.